In Vitro Antioxidant and Anticancer Properties of Various E. senegalensis Extracts - Souleymane Fofana; Cédric Delporte; Rafaèle Calvo Esposito; Moussa Ouédraogo; Pierre Van Antwerpen; Innocent Pierre Guissou; Rasmané Semdé; Véronique Mathieu (Molecules, 2022)
Although Erythrina senegalensis is a plant widely used in traditional medicine in sub-Saharan Africa, its biological properties have been poorly investigated to date. We first characterized by conventional reactions the composition of several stem bark extracts and evaluated in acellular and cellular assays their pro- or antioxidant properties supported by their high phenolic and flavonoid content, particularly with the methanolic extract. The pro- or antioxidant effects observed did not correlate with their IC50 concentrations against five cancer cell lines determined by MTT assay. Indeed, the CH2Cl2 extract and its ethyl acetate (EtOAc) subfraction appeared more potent although they harbored lower pro- or antioxidant effects. Nevertheless, at equipotent concentration, both extracts induced ER- and mitochondria-derived vacuoles observed by fluorescent microscopy that further led to non-apoptotic cell death. LC coupled to high resolution MS investigations have been performed to identify chemical compounds of the extracts. These investigations highlighted the presence of compounds formerly isolated from E. senegalensis including senegalensein that could be retrieved only in the EtOAc subfraction but also thirteen other compounds, such as 16:3-Glc-stigmasterol and hexadecanoic acid, whose anticancer properties have been previously reported. Nineteen other compounds remain to be identified. In conclusion, E. senegalensis appeared rich in compounds with antioxidant and anticancer properties, supporting its use in traditional practice and its status as a species of interest for further investigations in anticancer drug research.